1999
DOI: 10.1002/(sici)1097-0134(19990201)34:2<155::aid-prot1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Structure of catalase HPII fromEscherichia coli at 1.9 � resolution

Abstract: Catalase HPII from Escherichia coli, a homotetramer of subunits with 753 residues, is the largest known catalase. The structure of native HPII has been refined at 1.9 A ˚ resolution using X-ray synchrotron data collected from crystals flash-cooled with liquid nitrogen. The crystallographic agreement factors R and R free are respectively 16.6% and 21.0%. The asymmetric unit of the crystal contains a whole molecule that shows accurate 222-point group symmetry. The structure of the central part of the HPII subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 29 publications
7
71
0
Order By: Relevance
“…4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24). All of the three proteins have flavodoxin-like Rossmannfolds and belong to the Class I glutamine amidotransferase-like superfamily (GAT superfamily) involving thiJ domains (17).…”
Section: Resultssupporting
confidence: 76%
“…4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24). All of the three proteins have flavodoxin-like Rossmannfolds and belong to the Class I glutamine amidotransferase-like superfamily (GAT superfamily) involving thiJ domains (17).…”
Section: Resultssupporting
confidence: 76%
“…The two proteins with the highest Z scores are the noncatalytic domain of E. coli catalase HPII which has no known function (18), and the glutamine amidotransferase (GA) domain of GMP synthetase (19). Fig.…”
Section: Resultssupporting
confidence: 60%
“…Specific channels conducting small substrates or product molecules like oxygen, hydrogen peroxide, and perhaps water to and from the heme active site have been discerned in many enzymes (ref. 43 and references therein), including cytochrome c oxidase aa 3 (39). More specifically, ferrous heme b 595 may provide a transient binding site for the ligand on its way from heme d to the medium in analogy to Cu B in the heme-copper oxidases (44).…”
Section: Bandshift Of Heme B595 Induced By Co Binding To Heme Dmentioning
confidence: 99%